Rate of growth of nail. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
On September, 2, 2009 this well on in years man underwent a trauma on the nail matrix of the third left finger. On September, 20, after 18 days a transversal red-brownish line is evident level with the lunula (Fig. 1). In the subsequent figures the distal progression of the red-brownish line during the following weeks can be seen. From the day of the trauma the red-brownish line takes six months to move distally and reach the free border (Fig. 9). This is the rate of growth of the nail of the examined man. Starting from the third month, you can see a white, filamentous escort that follows the hemorrhagic line, moving distally with the same speed. We are probably dealing with parakeratosis secondary to trauma.